Arctiin Protects Chondrocytes from Interleukin-1β-Induced Inflammation and Apoptosis by RNA Sequence In vivo and In vitro - Yong-Jia Song; Jia-Min Bao; Zeng-Qiao Zhang; Yun-Xiang Hai; Hao-Nan Wen; Tian-Jun Zhai; Wei Feng; Min Song (World Journal of Traditional Chinese Medicine, 2024)
Objective: Osteoarthritis (OA) is a progressive joint disease characterized by degeneration and destruction of articular cartilage. Arctiin (ARC) has been shown in many studies to have potential anti-inflammatory, anti-apoptotic, and antioxidant effects in various diseases. However, the mechanism by which ARC exerts its protective effects in OA is not fully understood. Here, we explore the mechanism by which ARC plays its protective role in OA. Materials and Methods: Mouse chondrocytes were isolated and characterized through toluidine blue staining and collagen II immunofluorescence labeling. A mouse-based experimental model was developed to induce chondrocyte inflammation through Interleukin-1β (IL-1β). Subsequently, ARC was administered in various doses to mitigate this inflammation. Techniques such as biochemical assays, Enzyme-linked immunosorbent assay, quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, and immunofluorescence labeling were employed to detect changes in nitric oxide (NO), lactate dehydrogenase (LDH), inflammatory markers, and components of the cartilage matrix in chondrocytes. RNA-sequencing (RNA-seq) was utilized to explore variations in gene expression among chondrocytes across different groups. The genes and signaling pathways that were identified underwent analysis through Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment studies. Validation of gene and protein expression was carried out using qRT-PCR, Western blotting, and cellular flow cytometry, based on the results from sequencing. Furthermore, Safranin-O fast green staining and immunohistochemistry staining were performed on slices of the mice knee joint to evaluate the OA Research Society International score, alterations in the cartilage matrix, and levels of apoptosis-related proteins at sites of knee cartilage damage in an arthritis model induced by monosodium iodoacetate (MIA) and physical activity. Results: It was found that ARC effectively inhibits the production of IL-1β-induced chondrocytes’ inducible NO synthase, cyclooxygenase-2, NO, LDH, IL-6, and tumor necrosis factor-α. ARC exhibited a dose-dependent effect on chondrocytes by reducing IL-1β-induced matrix metalloproteinase-3 (MMP-3) and a disintegrin and metalloproteinase with thrombospondin motifs-5 levels while increasing Aggrecan levels. RNA-seq and bioinformatics analysis revealed that ARC’s therapeutic effects involve apoptotic signaling pathways through the downregulation of Bcl-2-associated X protein (Bax) and caspase-3 expression and the upregulation of B-cell lymphoma-2 (Bcl-2) expression in IL-1β-induced chondrocytes. ARC significantly raised the levels of aggrecan and Bcl-2 and decreased the levels of MMP-3, Bax, and caspase-3 in an arthritis model induced by MIA and movement. Conclusions: Through RNA-seq, in vitro cell assays, and in vivo experiments, this research established the link between apoptosis and inflammation in the progression of OA and confirmed the protective effects of ARC on chondrocytes and its key targets. This highlights ARC’s therapeutic potential and its role in the development of treatments for OA.